Explaining the Historic Rise in Financial Profits in the U.S. Economy - Ivan Mendieta-Mu\~noz; Costas Lapavitsas (The University of Utah, Department of Economics, 2017)
The ratio of financial to non-financial profits in the US economy has increased sharply since the 1970s, the period that is often called the financialisation of capitalism. By developing a two-sector theoretical model the ratio of financial to non-financial profits is shown to depend positively on the net interest margin and the non-interest income of banks, while it depends negatively on the general rate of profit, the non-interest expenses of banks, and the ratio of the capital stock to interest-earning assets. The model was estimated empirically for the post-war period and the results indicate that the ratio has varied mainly with respect to the net interest margin, although non-interest income has also played a significant role. The results confirm that in the course of financialisation the US financial sector has been able to extract rising profits through interest differentials and non-interest income, while the general rate of profit has remained broadly constant.
Keywords: E11; E44; G20; 330; rise in financial profits; financialisation; U.S. economy